"Think entrepreneur – think male": the effect of reduced gender stereotype threat on women's entrepreneurial intention and opportunity motivation. Issue 4 (8th March 2022) - Laguía, Ana; Wach, Dominika; Garcia-Ael, Cristina; Moriano, Juan A.
Abstract : Purpose: Entrepreneurship, which traditionally has been a male occupation, still attracts fewer women than men. Challenging gender stereotypes within entrepreneurship is one avenue to increase women's entrepreneurial intention and promote women entrepreneurship. This study adapts the "think manager – think male" leadership perspective to the entrepreneurship context and explores gender stereotype's implications for both entrepreneurial intention and motivation to become an entrepreneur. Design/methodology/approach: A total of 902 Spanish non-entrepreneurs, both male and female, were randomly asked about the representation of successful entrepreneurs (no-gender-mention), successful men entrepreneurs or successful women entrepreneurs (reduced stereotype threat condition vs no-gender-mention or men entrepreneurs' conditions). Then, female participants' entrepreneurial intention, its antecedents (i.e. attitudes toward entrepreneurship, subjective norms and entrepreneurial self-efficacy) and necessity vs opportunity motivation were measured and compared to their male counterparts' scores in those three conditions. Findings: Female participants reported higher entrepreneurial intention, self-efficacy and opportunity motivation when assigned to the successful women entrepreneurs' condition. Younger participants – compared to older ones – also exhibited higher entrepreneurial intention and opportunity motivation, more positive attitudes toward entrepreneurship and higher scores in subjective norms. Furthermore, findings suggest a woman entrepreneur seems to be less accessible (or more counter-stereotypical) to male participants than to female participants and, thus, the "think entrepreneur – think male" bias is more noticeable in male participants. Therefore, reducing negative stereotype threat for women in entrepreneurship may increase women's entrepreneurial career aspirations. This is of utmost importance to optimize training courses and mentoring programs to strengthen women's self-efficacy in their entrepreneurial skills and capabilities. Originality/value: This study contributes to the literature about gender, entrepreneurial intention and motivation by adapting a leadership paradigm ("think manager – think male") to entrepreneurship ("think entrepreneur – think male"). These findings shed new light on the antecedents of entrepreneurial intention and motivation and have implications for policy measures. Acknowledging that exposure to successful women entrepreneurs as role models potentially facilitates entrepreneurship among women, governments should provide tailor-made incentives and support for women entrepreneurs in the form of awareness raising, networking and in the mass media.